Analysis of the lipid profile and lifestyle of university students in the correlation with dyslipidemia and cardiovascular diseases - Vasconcelos, Bruna Cavalcante; Nazaré, Amanda de Oliveira; Gomes, Julye Layssa Gaia; Almeida, Marcella Kelly Costa de; Santos, Kemper Nunes dos (Seven Editora, 2024)
Lipids are essential molecules, responsible for regulatory and homeostasis functions. However, lifestyle can cause an imbalance in your metabolism, contributing to dyslipidemia and cardiovascular disease (CVD). Thus, the objective of this study was to analyze the lipid profile and lifestyle of university students as possible risk factors for dyslipidemia and CVD. A comparative analysis, of the prospective, qualitative and quantitative cross-sectional type, was carried out in 264 university students from different courses and academic semesters – Belém-Pará, having been followed from 03/2020 to 11/2022. Among the 264 participants, 37% were between the ages of 18 and 22 and 71.9% were women. 90.1% reported a busier routine after starting university, 79.5% changed eating habits, 53.7% started eating more at fast-foods and cafeterias, 38.6% reduced or stopped physical activities, in addition to 50% who were already sedentary before university, and 66.6% reported frequent alcoholism. Finally, 228 (86.3%) acknowledged the worsening of their quality of life after university. There were significant unfavorable differences (p < 0.05) in triglycerides, total cholesterol and fractions in the fourth and eighth semester students, mainly compared to freshmen, and veterans in the ninth and tenth semesters, suggesting a correlation between the university routine and a higher risk of dyslipidemia and CVD. DOI:https://doi.org/10.56238/sevened2024.001-027